2007
DOI: 10.1002/jnr.21567
|View full text |Cite
|
Sign up to set email alerts
|

α‐Amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionate attenuates glutamate‐induced caspase‐3 cleavage via regulation of glycogen synthase kinase 3β

Abstract: Preconditioning of sublethal ischemia exhibits neuroprotection against subsequent ischemia-induced neuronal death. It has been indicated that glutamate, an excitatory amino acid, is involved in the pathogenesis of ischemia-induced neuronal death or neurodegeneration. To elucidate whether prestimulation of glutamate receptor could counter ischemia-induced neuronal death or neurodegeneration, we examined the effect of alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA), an ionotropic subtype of glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
5
12
0
Order By: Relevance
“…d Relative optical density of Cytochrome C in cytosolic and mitochondrial of ischemic core and penumbra, which showed that translocation of Cytochrome C induced by cerebral ischemia was inhibited by administration of parecoxib. kinase-3b (GSK-3b) [22][23][24]. GSK-3b is regulated by phosphorylation at Ser 9 and Tyr 216 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…d Relative optical density of Cytochrome C in cytosolic and mitochondrial of ischemic core and penumbra, which showed that translocation of Cytochrome C induced by cerebral ischemia was inhibited by administration of parecoxib. kinase-3b (GSK-3b) [22][23][24]. GSK-3b is regulated by phosphorylation at Ser 9 and Tyr 216 .…”
Section: Discussionmentioning
confidence: 99%
“…As a downstream effect of Akt, glycogen synthase kinase 3b (GSK-3b) is phosphorylated or inactivated by Akt [20,21], and the phosphorylated Akt/GSK-3b provides neuroprotection against cerebral ischemic reperfusion injury in different animal models in vivo or in vitro [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…GSK3 also phosphorylates the postsynaptic protein PSD-95, which regulates AMPA receptor trafficking (Nelson et al, 2013). AMPA signaling, in turn, reduces GSK3 activity (Nishimoto et al, 2008), perhaps as a feed-back inhibitory mechanism for AMPA signaling, that also leads to reduced cell surface expression of the NMDA receptor subunit NR1 (Nishimoto et al, 2009). This interaction is consistent with the finding that GSK3 maintains the surface localization of NMDA receptors, including both the NR1 and NR2B subunits, by a mechanism that involves both Rab5 and PSD95 (Chen et al, 2007; Deng et al, 2014).…”
Section: Gsk3 Interactions With Receptors and Receptor-coupled Sigmentioning
confidence: 99%
“…Activation of Akt promotes cell survival by modulation of various downstream elements, including glycogen synthase kinase-3β (GSK-3β) and Bcl-2-associated death promoter (BAD) [12,13]. The phosphorylated Akt had been found to inhibit cell apoptosis and provide protection against hepatic I/R injury [14,15].…”
Section: Introductionmentioning
confidence: 99%